2021
DOI: 10.1007/s10147-021-01960-6
|View full text |Cite
|
Sign up to set email alerts
|

A phase I, single-center, open-label study of RM-1929 photoimmunotherapy in Japanese patients with recurrent head and neck squamous cell carcinoma

Abstract: Background To determine the safety, preliminary efficacy, pharmacokinetics, and immunogenicity of a single cycle of RM-1929 photoimmunotherapy, an anti-EGFR antibody cetuximab conjugated with a light-activatable dye (IRDye®700DX), in Japanese patients with recurrent head and neck squamous cell carcinoma (rHNSCC). Methods Patients received a single fixed dose (640 mg/m2) of RM-1929 and a fixed light treatment dose (50 J/cm2 for superficial illumination; 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…As for the efficacy, the ORR was 89%, and the DCR was 100%. A phase I/IIa multicenter, open-label study on HN-PIT reported the recommended dose, safety, and therapeutic efficacy [ 7 , 15 ]. The primary objective of the phase I part was to determine the recommended dose of RM-1929 and optimal laser light intensity under fixed-light intensity.…”
Section: Discussionmentioning
confidence: 99%
“…As for the efficacy, the ORR was 89%, and the DCR was 100%. A phase I/IIa multicenter, open-label study on HN-PIT reported the recommended dose, safety, and therapeutic efficacy [ 7 , 15 ]. The primary objective of the phase I part was to determine the recommended dose of RM-1929 and optimal laser light intensity under fixed-light intensity.…”
Section: Discussionmentioning
confidence: 99%
“…NIR-PIT causes minimal damage to normal cells due to the fact of its specific molecular targeting properties. However, in actual clinical practice, the formation of local edema around the tumor was observed early after treatment [ 24 , 25 ]. This edema is likely caused by ROS that is associated with acute inflammation caused by tumor or surrounding normal tissue damage [ 26 , 27 ], because such edema was suppressed by using reducing agents including ascorbic acid [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tumors deep within the body are difficult to treat using a frontal light diffuser alone. A cylindrical light diffuser-fiber inserted into the treatment site can overcome this limitation by bringing light to the center of the tumor [ 10 , 14 , 33 , 34 ]. Using a cylindrical light diffuser, NIR light can be delivered in a cylindrical pattern (radially 1 cm from the probe for a total distance of 2 cm) to practically any tumor site via a needle, catheter, or endoscope.…”
Section: Nir-pitmentioning
confidence: 99%